Role of Calcineurin Inhibitors in the Management of Atopic Dermatitis in Children - Kamilla E. Efendieva; Leyla S. Namazova-Baranova; Juliya G. Levina; Vera G. Kalugina; Anna A. Alekseeva; Elena A. Vishneva; Konstantin S. Volkov (Вопросы современной педиатрии)
Atopic dermatitis (AD) is a widespread chronic inflammatory skin disease that has a significant impact on various aspects of patient's life. This review presents modern view on AD pathophysiology, its correlation with other concomitant diseases, and covers practical aspects of external anti-inflammatory therapy implementation. The analysis of clinical studies has shown the significant role of calcineurin inhibitors in the effective treatment of AD in children from its first manifestations at early age.